High Yield Syngas and Performance of Ni-loaded Thai Lignite Char Catalyst from Sawdust Gasification - Suparin Chaiklangmuang (Science Faculty of Chiang Mai University, 2019)
Catalytic steam gasification of sawdust was performed with a steam pressure of 30 kPa, catalyst/biomass mass ratios of 0.5-3.0 and reaction temperatures of 500-650 °C. The Ni-loaded Thai lignite char catalyst, 15.50 wt%, was effective in catalyzing the volatile matters and tars from the devolatilizer and promoting syngas formation. The yield of H2 increased mostly with increase in temperature throughout the investigations, while that of CO showed a decreasing trend, from 500-550 °C, leveling off afterward. The highest H2 yield, 60.98%, was obtained at the final gasification temperature of 600 °C. The ratios of H2/CO obtained in the reaction temperature study were between 1.08 and 2.07. The effect of the catalyst/biomass mass ratio was investigated at 600 °C; the ratio 3.0 achieved the maximum H2/CO ratio, at 2.33. Considering the experimental results, there exists good potential for syngas production from sawdust via catalytic steam gasification using Ni-loaded Thai lignite char catalyst.